Philanthropy in the world's traditions - Ilchman, Warren Frederick; Katz, Stanley Nider; Queen, Edward L. (Philanthropic studies., 1998)
An investigation of how cultures outside the Western tradition understand philanthropy and how people in these cultures attempt to realize "the good" through giving and serving. These essays study philanthropy in Buddhist, Islamic, Hindu, Jewish, and Native American religious traditions and in cultures from Latin America, Eastern Europe, the Middle East, Africa, and Asia.